The Effect of Promotion on the Sales of S3shop MSMES in Conggeang District, West Java - Lala Nurhayati; Anne Lasminingrat; Maria Lusiana Yulianti; Deden Komar Priatna (DINASTI RESEARCH, 2021)
In this study there are two variables, namely Promotion as a free variable and sales as a bound variable. This research was conducted to be able to find out the effect of sales on S3shop MSMEs in Conggeang Kecaatan, West Java, and to find out how much influence promodi has on sales. The methods used in this study are descriptive and verificative methods, data collection techniques obtained from primary data, namely through interviews and questionnaires. While secondary data is obtained from books, journals, the internet. To determine the magnitude of the effect of promotion on satisfaction, statistical analysis with a simple Linear Regression formula and Coefficient of Determination was used using the IBM 25 SPSS program. Based on the results of the discussion on Promotion Against Sales and based on the results obtained from the questionnaire answers, it turns out that the Promotion of Sales of S3shop MSMEs as a whole is very good because it shows a positive response. For the Effect of Promotion on Msme sales, a statistical test is used, based on calculations, it can be concluded that there is a very good influence between Promotion on Sales on S3shop MSMEs of 29.2% while the remaining 7.8% is influenced by Other factors.